Metabolic diversity in a collection of wild and cultivated Brassica rapa subspecies - Zheng, Shuning; Szymański, Jędrzej; Shahaf, Nir; Malitsky, Sergey; Meir, Sagit; Wang, Xiaowu; Aharoni, Asaph; Rogachev, Ilana (Frontiers in Molecular Biosciences, 2022)
Brassica rapa (B. rapa) and its subspecies contain many bioactive metabolites that are important for plant defense and human health. This study aimed at investigating the metabolite composition and variation among a large collection of B. rapa genotypes including subspecies and their accessions. Metabolite profiling of leaves of 102 B. rapa genotypes was performed using ultra-performance liquid chromatography coupled with photodiode array detector and quadrupole time-of-flight mass spectrometry (UPLC-PDA-QTOF-MS/MS). In total 346 metabolites belonging to different chemical classes were tentatively identified; 36 out of them were assigned with high confidence using authentic standards and 184 were those reported in B. rapa leaves for the first time. The accumulation and variation of metabolites among genotypes were characterized and compared to their phylogenetic distance. We found 47 metabolites, mostly representing anthocyanins, flavonols and hydroxycinnamic acid derivatives that displayed a significant correlation to the phylogenetic relatedness and determined four major phylometabolic branches; (a) Chinese cabbage, (b) yellow sarson and rapid cycling, (c) the mizuna-komatsuna-turnip-caitai; and (d) a mixed cluster. These metabolites denote the selective pressure on metabolic network during B. rapa breeding. We present a unique study that combines metabolite profiling data with phylogenetic analysis in a large collection of B. rapa subspecies. We show how selective breeding utilize the biochemical potential of wild B. rapa leading to highly diverse metabolic phenotypes. Our work provides the basis for further studies on B. rapa metabolism and nutritional traits improvement.